Intrathecal baclofen pump failure: case report - Oliveira, Mónica (Journal of the Portuguese Society of Anesthesiology, 2022)
Intrathecal baclofen pumps have been used for the treatment of refractory spasticity and are increasing in number. It is not hard to understand that the complications associated with these devices are increasing too, despite they remain rare. Here we present a case report of a young woman with an intrathecal baclofen pump implanted for a few years that experienced a recrudescence of spasticity. After excluding the most common causes of this alteration and after the infused dose has been increased without improvement of the symptoms, our team performed a surgical review. During the procedure we discover three rupture points upstream the connexion piece, with active extravasation of a clear liquid. This case report shows the importance of clinical suspicion and the rapid treatment of the complications associated with these devices.